Analysis of the correlation between ICT and Tax Revenue in Indonesia - Yustisia Purba Nugrahani; Benedictus Raksaka Mahi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This research aims to analyze the impact of ICT utilization in tax collection at the national, provincial and district/city levels. This research focuses on how far the impact of ICT utilization in increasing tax revenue. Based on that, this research recognizes three econometric models, namely central, provincial and district/city tax revenue models which analyzed through Fixed Effect Model (FEM) and Random Effect Model (REM) then selected by Hausman test. The results indicate that on average, an increase in SMEs using ICT with IP-ICT level 5, will increase the central tax ratio, then an increase in motorized vehicles whose owners use ICT with IP-ICT level 5, will increase the provincial tax ratio, an increase in Gross Regional Domestic Product of the hotel and/or restaurant sector whose owners/managers use the ICT with IP-ICT level 5, will increase district/city tax ratio. The implication of this research, Central Government needs to socialize the use of ICT-based tax applications, Provincial Government should coordinate with local police in disseminating the use of online tax applications for motor vehicle tax, District/City Governments periodically socialize the obligation to use the tapping box or online cash register machine.